Image Quality of Radiography Orthoview in Osteoarthritis of Knee using Suphan Model 4.0 - Kowsomjeen, Katcharin (Journal of Health Science of Thailand, 2019)
This study was conducted to explore the image quality and cost of orthoview radiography using a radiographic apparatus - the Suphan Model 4.0. The study materials were 35 samples of radiographies of Knee AP standing and orthoview taken from osteoarthritis patients who had total knee arthroplasty (TKA) preparation in Chaophrayayommarat Hospital, Suphaburi Province, from April to June 2017. The samples were evaluated by three orthopedists. Descriptive statistics was used for the analysis of the data, applying seven quality criteria. The study was conducted in two phases: a preliminary phase and a study phase. The preliminary phase was evaluated by one technician and two radiologists. It tested the strength and safety of Suphan Model 4.0. It was found that both strength and safety were good by all six criteria (mean=4.33–4.67). The total score of strength and safety accordingly had a mean±SD of 4.56±0.577. The image quality of Suphan Model 4.0 was evaluated by three orthopedists, based on the images of six skeletons. The findings of this evaluation indicated a good quality - with a mean±SD of 4.51±0.0445. The second phase tested the image quality of Suphan Model 4.0, which was evaluated by three orthopedists based on the images of 35 osteoarthritis patients who had TKA preparation. The findings of this evaluation indicated a good quality as well. The percentage of image quality was 88.6%, and the mean±SD of 8.86±0.665. The images were good by all seven quality criteria. (mean=8.27-9.35) The images were grouped in three quality levels, i.e. good, poor, and rejected, and the findings revealed 90.5 percent of the images were of good qualityand 9.5 percent of poor quality. Finally, the cost for Suphan Model 4.0 was significantly less than that of installing an X-ray machine (9’690 vs 3’500’000 Bahts) while the running costs of using Suphan Model 4.0 were also low.